Development of Transport Service Management under the Conditions of European Integration (Economics and region, 2021)
The transport system of Ukraine, which consists of transport infrastructure, vehicles and management system, is studied in this paper. The dynamics of cargo transportation by all types of vehicles and the structure of exports and imports of transport services in Ukraine are analyzed. It is proved that transport logistics should include tasks, the solution of which will allow optimizing both transport processes and processes related to them. It is distinguished that one of the priority tasks of Ukraine in the conditions of European integration is the dynamic development of the domestic transport system with the help of smart technologies.
Keywords: development; logistics; management; optimization; rolling stock; transportation; transport services